Holistic Learning in Engineering: A NEP-Driven Exploration of Emerging Technologies for Education Transformation - Tanna, Paresh; Lathigara, Amit; Bhatt, Nirav (Journal of Engineering Education Transformations, 2025)
The New Education Policy (NEP) introduced by the Government of India aims to revolutionize engineering education by promoting a more holistic and contemporary approach. This paper explores the integration of emerging technologies, such as artificial intelligence (AI) and machine learning (ML), Internet of Things (IoT), and data analytics and visualization, into engineering education. The study examines how these technologies can help to enhance learning experiences by offering flexibility, personalization, and hands-on engagement. Through effective collaboration, skill development, and experiential learning, these pedagogies prepare engineering students to meet the evolving demands of the modern world. The successful implementation of these technologies requires careful planning, faculty training, and addressing challenges related to accessibility and inclusivity. The findings highlight that the integration of these emerging technologies aligns with the NEP's vision, thereby empowering engineering education to cater to diverse student needs and equip them with future-ready skills.